(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Scientific literacy is a very important competency to pay attention to so that students can use science in their lives. The results of teacher interviews stated that scientific literacy learning at SMP Negeri 10 Payakumbuh was still not being implemented optimally. There needs to be a learning model that supports students’ scientific literacy, one of which is the Reading to Learn (R2L) model. This research aims to determine the effect of the Reading to Learn learning model on the scientific literacy of students at SMP Negeri 10 Payakumbuh on Ecology and Biodiversity material. The type of research used in this research is quasi-experimental with a quantitative approach. The research design used was Posttest Only Control Group Design. This research design involves two groups, namely the experimental group which will receive treatment applying the R2L model in learning and the control group which will receive conventional learning. The data obtained were analyzed using normality tests, homogeneity tests, and hypothesis tests.